A multi-solid waste synergistic geopolymer composite material and a preparation method thereof
Patent Information
- Application Number
- CN202611165495.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-03
AI Technical Summary
[0008]本发明的目的在于针对现有传统超高强混凝土碳排放高、制备成本高昂,以及常规碱激发地聚物材料基体孔隙缺陷多、密实性不足、脆性大、易开裂、骨料界面结合差、缓凝体系功能单一、钢纤维易锈蚀、综合性能不均的技术问题,提供一种多固废协同地聚物复合材料及其制备方法
[0019]本发明的主要有益效果包括:
Smart Images

Figure REF-OBJ-1785397256603-000001
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials and concrete preparation technology, specifically to a multi-solid waste synergistic geopolymer composite material and its preparation method. Background Technology
[0002] As domestic infrastructure construction extends into special engineering fields such as super high-rise buildings, long-span bridges, undersea tunnels, deep-water wharves, and civil defense and military protection, major infrastructure projects have put forward composite rigid indicators for concrete used in load-bearing structures, including ultra-high compressive strength, high impact toughness, excellent workability, and low carbon and durability. Ultra-high performance concrete with a compressive strength of not less than 120MPa has become an essential core building material for special protection and marine corrosion environment engineering.
[0003] Current ultra-high performance concrete systems mostly use high-content silicate cement as the core cementitious phase, relying on ultra-low water-cement ratios combined with ultra-fine mineral admixtures to achieve ultra-high mechanical strength. However, this technical route has intractable technical shortcomings: First, the calcination of cement clinker consumes a lot of energy and emits huge amounts of carbon, which is not conducive to the resource utilization of industrial solid waste. Second, cement-based materials are brittle, and shrinkage cracks and long-term corrosion and aging problems are difficult to eliminate. Third, the aggregates are highly dependent on natural crushed stone mined from mountains, and the continuous consumption of sand and gravel resources exacerbates ecological damage, mining and transportation costs are rising year by year, and the overall preparation cost is relatively high.
[0004] While existing cement-free alkali-activated geopolymer materials can significantly reduce carbon emissions, conventional industry solutions still heavily utilize natural crushed stone as coarse aggregate, failing to fully leverage the potential for solid waste resource utilization. The mismatch in elastic modulus between natural aggregate and silica-alumina gel, the weak interfacial transition zone, and the tendency for stress concentration under stress severely limit the material's strength from consistently exceeding 120 MPa. Completely removing coarse aggregate to prepare pure fine-grained ultra-high-strength geopolymers would require a significant increase in the dosage of cementitious powder and alkali activator, drastically raising raw material costs and resulting in extremely low cost-effectiveness for engineering projects.
[0005] With the advancement of industrialization, a large amount of waste corundum aggregate has been generated. Long-term open-air stockpiling occupies a large amount of land, and leachate easily pollutes the soil and groundwater. The resource utilization of solid waste coarse aggregate can not only realize the disposal of large-scale solid waste, but also reduce the mining of natural sand and gravel at the source, which is in line with the policy guidance of green building materials. At the same time, its recycling and purchase price is much lower than that of natural crushed stone, which can significantly reduce raw material costs. However, the existing supporting technologies for solid waste coarse aggregate are not perfect. There is a lack of integrated synergistic solutions for controllable shaping of aggregate morphology, interface strengthening, and system retarding and toughening. Solid waste coarse aggregate generally has defects such as high porosity, sharp edges and corners, and weak interfacial bonding, making it difficult to stably prepare high-performance multi-solid waste synergistic geopolymers, and failing to simultaneously take into account environmental value, economic advantages and performance.
[0006] Specifically, existing alkali-activated geopolymer materials still have several technical shortcomings: (1) The natural crushed stone aggregate and geopolymer gel have poor compatibility, and the interface transition zone has obvious defects. To avoid this problem, existing technologies mostly completely remove coarse aggregate, but this leads to a significant increase in the amount of cementitious materials and alkali activators used, resulting in increased costs. (2) Commonly used retarders are mainly single additives such as borax, sodium gluconate, and citric acid. The retardation effect decays rapidly at high temperatures, and the strength is prone to shrinkage in the later stage. Moreover, they only have a single retardation effect and cannot simultaneously refine the pores and improve the impermeability and wear resistance. (3) Ordinary copper-plated steel fibers are directly incorporated into high-alkali matrices. They are prone to corrosion under long-term dry and wet cycles and chloride ion erosion, causing the fiber and matrix interface to debond, and the toughness and durability to continuously decrease. Existing modification methods such as galvanizing and epoxy coating are prone to dissolution and failure in strong alkaline environments. There is a lack of low-cost inorganic passivation pretreatment processes suitable for high-alkali geopolymers.
[0007] Therefore, developing a multi-solid waste synergistic geopolymer composite material (GEC) with scientific formulation, simple process, stable and controllable performance, and green and low carbon emissions, while simultaneously solving three major problems such as weak aggregate interface, single function of retarding system, and long-term corrosion of steel fibers, has important theoretical research value and practical engineering application significance for realizing efficient resource utilization of industrial solid waste and meeting the needs of major special engineering construction. Summary of the Invention
[0008] The purpose of this invention is to address the technical problems of existing traditional ultra-high strength concrete, such as high carbon emissions and high preparation costs, as well as conventional alkali-activated geopolymer materials, such as numerous matrix pore defects, insufficient density, high brittleness, easy cracking, poor aggregate interface bonding, single function of retarding system, easy corrosion of steel fibers, and uneven comprehensive performance, by providing a multi-solid waste synergistic geopolymer composite material and its preparation method.
[0009] To achieve the above-mentioned objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a multi-solid waste synergistic polymer composite material, comprising, by weight, the following raw materials: 280 parts blast furnace slag, 200 parts fly ash, 60 parts silica fume, 60 parts metakaolin, 265 parts composite alkali activator, 300 parts quartz sand, 200 parts solid waste powder, 850-950 parts shaped aggregate, 0-22 parts nano calcium carbonate, 25 parts polycarboxylate superplasticizer, 2 parts organosilicon liquid defoamer, 39-117.75 parts modified steel fiber, and 0.36-0.75 parts composite retarder; The composite alkali activator is composed of a NaOH solution and a sodium silicate solution in a mass ratio of 17:36. The shaped aggregate is obtained by shaping solid waste coarse aggregate through a two-stage controllable ball mill. The projection is a polygonal shape with smooth transitions at the edges and corners. The radius of the rounded transition at the edges and corners is 0.3 to 1.2 mm, and the surface has a textured surface. The solid waste powder is the powder obtained by air separation during the ball milling and shaping process of the solid waste coarse aggregate. The modified steel fiber has a passivation film on its surface; The composite retarder is composed of 0.3 to 0.6 parts of strontium nitrate and 0.06 to 0.15 parts of potassium fluorozirconate.
[0010] Preferably, in the composite alkali activator, the concentration of the NaOH solution is 12 mol / L, and the modulus of the sodium silicate solution is 3.2.
[0011] Preferably, the shaped aggregate is prepared by the following process: a mixture of cylindrical ceramic segments and triangular prism ceramic segments is used as the grinding medium, the mass ratio of solid waste coarse aggregate to grinding medium is 1:0.7 to 1.0, and it is ground in two stages. The linear speed of the first stage of grinding is 1.5 to 1.6 m / s, and the grinding time is 12 to 18 min, which is used to passivate the sharp edges and corners of the solid waste coarse aggregate and form an uneven surface. The linear speed of the second stage of grinding is 1.2 to 1.4 m / s, and the grinding time is 5 to 8 min, which is used to remove burrs from the edges and corners.
[0012] Preferably, the solid waste coarse aggregate is waste brown fused alumina aggregate, and the solid waste micro powder is ball-milled brown fused alumina micro powder.
[0013] Preferably, the modified steel fiber is prepared by the following process: using copper-plated steel fiber with a diameter of 0.18 mm and a length of 15 mm as the substrate, the fiber is ultrasonically cleaned with anhydrous ethanol for 5 min to remove oil, dried at 105°C, immersed in a 5% sodium hydroxide solution at room temperature for 20 min for alkaline etching, washed with water to remove surface alkali, and then immersed in a 5% sodium silicate aqueous solution for 5 min. Finally, it is dried at a low temperature of 60-70°C to obtain the modified steel fiber with a passivation film on the surface.
[0014] Preferably, the nano-calcium carbonate has an average particle size of 30–80 nm and a specific surface area of 350–450 m². 2 / kg, CaCO3 content ≥97%; The particle size of the solid waste powder is 200-600 mesh.
[0015] Preferably, the blast furnace slag is S95 grade water-quenched granulated blast furnace slag powder with a specific surface area of 420-460 m². 2 / kg; The fly ash is Grade I low-calcium fly ash, with free calcium oxide ≤1.0% and a specific surface area of 380–430 m². 2 / kg; The silica fume has a SiO2 content of ≥92% and an average particle size of 0.1–0.3 μm; The metakaolin is obtained by calcining kaolin at 600℃ for 2 hours, and the content of amorphous active aluminum phase is ≥85%.
[0016] Secondly, the present invention also provides a method for preparing a multi-solid waste synergistic geopolymer composite material, which includes the following steps: Step (1) Preparation of composite alkali activator: Mix NaOH solution and sodium silicate solution evenly to obtain composite alkali activator; Step (2), solid phase pre-dispersion: add metakaolin, fly ash, silica fume, quartz sand, solid waste powder, shaped aggregate, nano calcium carbonate, composite retarder and modified steel fiber into a mixer and dry mix and disperse. Step (3), Liquid phase mixing: The composite alkali activator, polycarboxylate superplasticizer and organosilicon liquid defoamer are premixed evenly, poured into a mixer and stirred evenly; Step (4) Add blast furnace slag: After step (3) is completed, add blast furnace slag and stir to mix well; Step (5) Molding and curing: Transfer the mixture obtained in step (4) into the mold, vibrate it, cover the surface with a film, let it stand, demold it, and cure it to the specified age.
[0017] Preferably, in step (2), the dry mixing speed is 70 r / min and the time is 2 min; In step (3), the stirring speed is 90 r / min and the time is 4 min; In step (4), the stirring speed after adding blast furnace slag is 150 r / min and the time is 3 min.
[0018] The core technical principle of this invention is as follows: (1) This invention uses blast furnace slag, fly ash, silica fume, and metakaolin as cementing materials, and uses NaOH solution and sodium silicate solution to form a composite alkali activator. NaOH provides a high alkalinity environment to promote the breaking and dissolution of Si-O and Al-O bonds in the cementing materials; sodium silicate adjusts the silicon-alkali ratio of the system and provides added soluble silicon. The two work together to make the active components condense to form C-(N)-ASH type composite gel, which constitutes the matrix of the composite material. (2) Solid waste coarse aggregate (particle size 5-20mm) is shaped into shaped aggregate after being shaped by a two-stage controllable ball mill. The grinding media is a mixture of cylindrical ceramic segments and triangular prism ceramic segments. The cylindrical segments are in "line contact" with the solid waste coarse aggregate, and the triangular prism segments are in "edge contact" with the solid waste coarse aggregate. The two different contact forms produce uneven cutting, scraping and squeezing effects on the surface of the solid waste coarse aggregate. The first stage of grinding uses a high linear speed (1.5-1.6 m / s) to cut and blunt the sharp edges of the coarse aggregate from solid waste, eliminating the source of stress concentration under load. During this process, the local impact and grinding action of the grinding media on the surface of the coarse aggregate from solid waste causes micro-fracture and peeling of the aggregate surface, forming an irregular uneven surface. At the same time, there are hardness differences between different mineral phases inside the coarse aggregate from solid waste. The soft phase peels off preferentially during the grinding process, while the hard phase protrudes relatively, further enhancing the roughness of the surface. The second stage of grinding uses a low linear speed (1.2-1.4 m / s) to lightly polish only the edges and corners to remove the burrs generated by grinding and avoid excessive grinding that damages the already formed uneven surface. The resulting aggregate has blunted edges and a rough surface, which not only eliminates stress concentration but also strengthens the mechanical interlocking between the aggregate and the matrix, improving the bonding quality of the aggregate-matrix interface. (3) After being etched by sodium hydroxide solution and treated with sodium silicate solution, copper-plated steel fibers form a passivation film on their surface. The passivation film, with a silicon-oxygen network as its framework, has good chemical compatibility with the geopolymer matrix. It can isolate high-alkalinity matrices and chloride ions, thereby inhibiting steel fiber corrosion from the source and preventing fiber-matrix interface debonding. After surface treatment, the modified steel fibers are uniformly dispersed in the matrix to form a spatial lap network. When the matrix is tensile and cracked, the fibers transmit stress across the crack surface, preventing the crack from opening further by bridging. At the same time, energy is dissipated through frictional slippage at the fiber-matrix interface, thereby improving the intrinsic brittleness of the geopolymer and effectively inhibiting the propagation of microcracks in the matrix. (4) Strontium nitrate and potassium fluorozirconate are combined to form a composite retarder. Potassium fluorozirconate dissociates into [ZrF6] in water. 2- This complexed anion can react with Al in the liquid phase. 3+ Complexation occurs, reducing the effective concentration of the aluminum source participating in the geopolymerization reaction; strontium nitrate provides Sr 2+It can be physically adsorbed on the surface of cementitious particles or form insoluble products, thus delaying the contact reaction between particles and alkaline solution. The two are combined to delay the polymerization reaction rate through two pathways: liquid phase ion concentration and particle surface state, thus extending the slurry construction window period. (5) Solid waste micro powder (micron-sized, 200-600 mesh) and nano calcium carbonate (nano-sized, 30-80 nm) form a "nano-micro" dual-scale filling system, which fills the pores of different scales in the matrix in layers, refines the pore size, and reduces the overall porosity. At the same time, solid waste micro powder and quartz sand form a close packing gradation, which optimizes the packing density at the aggregate level and further reduces the matrix porosity. (6) This invention adopts the blast furnace slag delayed feeding process. The "delayed feeding" refers to delaying the addition of highly active components to the stirring system, so that they can participate in the reaction after the other components are fully dispersed. Since blast furnace slag has high activity, if it is added together with other dry materials, it will come into contact with the composite alkali activator in advance and react rapidly, resulting in a rapid loss of slurry fluidity. This invention adds blast furnace slag after the liquid phase is mixed, effectively avoiding premature reaction, thereby extending the construction window and avoiding problems such as pipe blockage and casting dead zones caused by early rapid reaction.
[0019] The main beneficial effects of this invention include: (1) In this invention, blast furnace slag, fly ash, silica fume and metakaolin completely replace cement clinker as cementing material, and waste brown corundum is used as solid waste coarse aggregate. After being shaped by two-stage controllable ball milling, shaped aggregate is obtained, which replaces natural crushed stone as coarse aggregate component. The comprehensive utilization rate of solid waste is high, the raw material cost is significantly reduced, and the high energy consumption and high carbon emissions of cement calcination are avoided.
[0020] (2) Solid waste coarse aggregate is shaped by a two-stage controlled ball mill: the first stage of grinding blunts sharp edges and corners, eliminates stress concentration at sharp corners under load, and avoids early induction of microcracks; the second stage of grinding removes burrs from the edges and corners, retaining the uneven surface formed by micro-fracture and selective abrasion, rather than grinding it into a smooth spherical surface, thereby strengthening the mechanical interlocking effect between the aggregate and the matrix. At the same time, the ball mill by-product solid waste powder replaces part of the quartz sand, and its particle size forms a close packing gradation with the remaining quartz sand, effectively filling the voids between the aggregates and reducing the porosity of the matrix. The synergistic effect of the above aggregate shaping and gradation optimization makes the matrix more compact and significantly improves the mechanical properties.
[0021] (3) After surface treatment, the modified steel fibers are uniformly dispersed in the matrix to form a continuous and stable spatial lap network. When the matrix is tensile and cracked, the fibers transmit stress across the crack surface and prevent the crack from opening further by bridging. At the same time, energy is dissipated through frictional slip at the fiber-matrix interface, thereby improving the intrinsic brittleness of the geopolymer, effectively inhibiting the propagation of microcracks in the matrix, and improving the toughness and crack resistance of the composite material.
[0022] (4) This invention uses strontium nitrate and potassium fluorozirconate to form a composite retarder, which is then used to retard the coagulation process. 2+ and [ZrF6] 2- The synergistic complexation effect slows down the polymerization reaction rate from two aspects: liquid phase ion concentration and particle surface state, significantly extending the slurry construction window period.
[0023] (5) Solid waste micro powder (micron-sized, 200-600 mesh) and nano-calcium carbonate (nano-sized, 30-80 nm) form a "nano-micro" dual-scale filling system, which fills the pores of different scales in the matrix in layers, refines the pore size, reduces the overall porosity, and makes the matrix more compact. Solid waste micro powder also forms a close packing gradation with quartz sand, further optimizing the packing density at the aggregate level.
[0024] (6) The delayed feeding process of blast furnace slag allows the highly active slag to be added after the liquid phase mixing is completed, avoiding premature contact with the composite alkali activator and the resulting rapid depolymerization and condensation reaction. This effectively extends the construction window and prevents problems such as loss of fluidity, pipe blockage, and dead corners in the pouring caused by excessively rapid early reaction. At the same time, the dry material premixing and dispersion process allows the modified steel fibers to be premixed and dispersed with various powders and aggregates. Relying on the barrier and lubrication effect of solid particles, it avoids the fibers from clumping and agglomerating due to the viscosity of the slurry when directly mixed in the liquid phase, ensuring uniform fiber distribution and fully exerting the toughening effect. Detailed Implementation
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to them. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials in the art. The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to these embodiments.
[0026] This invention provides a multi-solid waste synergistic polymer composite material, which, by weight, comprises the following raw materials: 280 parts blast furnace slag, 200 parts fly ash, 60 parts silica fume, 60 parts metakaolin, 265 parts composite alkali activator, 300 parts quartz sand, 200 parts solid waste powder, 850-950 parts shaped aggregate, 0-22 parts nano-calcium carbonate, 25 parts polycarboxylate superplasticizer, 2 parts organosilicon liquid defoamer, 39-117.75 parts modified steel fiber, and 0.36-0.75 parts composite retarder. The details of each raw material are described below.
[0027] The blast furnace slag is S95 grade water-quenched granulated blast furnace slag powder. Activity index ≥ 95% (28d); residue ≤ 10% on a 45μm square-hole sieve; specific surface area 420–460 m². 2 / kg; main chemical components are CaO 38%~43%, SiO2 25%~32%, Al2O3 12%~16%, MgO 6%~10%; glass content ≥90%, density 2.85~2.95g / cm³ 3 The fluidity ratio is ≥98%. Blast furnace slag is the main contributing component to the strength of the polymer in this invention. Its high CaO content and glassy structure allow it to rapidly dissociate into CaO under alkaline activation conditions. 2+ And active silicon-aluminum components, Ca 2+ The active silica-alumina components directly participate in the formation of the three-dimensional network gel, contributing to the formation of C-(N)-ASH gel. Therefore, the early reaction rate of blast furnace slag is relatively fast, providing higher early strength for the composite material. Simultaneously, the Ca in the slag... 2+ Al dissolved from fly ash and metakaolin 3+ Si 4+ A blended network of C-(N)-ASH gel and NASH gel is formed, with the two gels intertwined to make the matrix structure more compact, thereby improving the mechanical properties and durability of the material.
[0028] The fly ash is Class I low-calcium fly ash from power plant dry discharge. Residue on a 45μm sieve is ≤12%, and the specific surface area is 380–430 m². 2 / kg; Loss on ignition ≤5.0%, free calcium oxide ≤1.0%; Main active components are SiO2 48%~55%, Al2O3 22%~28%; Vitreous spherical particles account for ≥85%, density 2.10~2.30g / cm³ 3 In this invention, fly ash plays three main roles: First, its spherical particle shape acts as a "ball bearing" in the slurry, reducing frictional resistance between particles and thus improving slurry fluidity, which is beneficial for construction operations and uniform fiber dispersion. Second, its active silica-alumina components participate in the geopolymerization reaction under alkali activation, generating NASH gel, which fills the matrix pores and improves later-stage strength. Third, the reaction rate of fly ash is slower than that of blast furnace slag, delaying the geopolymerization process and helping to extend the construction window. The low-calcium characteristic of fly ash avoids excessive Ca... 2+ The resulting rapid solidification forms a complementary reaction mode of "fast and slow combination" with the blast furnace slag, enabling the matrix to achieve strength growth at different ages.
[0029] Metakaolin is obtained by calcining kaolin at 600℃ for 2 hours. It contains ≥85% amorphous active aluminum phase, 32%–38% active Al₂O₃, and 50%–56% SiO₂; the average particle size is 2–8 μm, and the specific surface area is 600–900 m². 2 / kg; pH value 7.5~9.0, density 2.55~2.65g / cm³ 3 It rapidly dissolves aluminum ions upon contact with alkali. The high content of active aluminum phase in metakaolin can rapidly dissolve Al under alkaline activation conditions. 3+ Al 3+ It enters the inter-chain space of silicon-oxygen tetrahedra in a four-coordinate manner to form Si-O-Al bonds, constructing a three-dimensional network structure, thereby significantly improving the early strength of the composite material. Metakaolin has the characteristic of rapidly dissolving aluminum ions when exposed to alkali, which can complement the aluminum source with blast furnace slag and fly ash, further optimizing the particle size distribution and reactivity of the cementitious system. The three components synergistically construct a more compact and stronger geopolymer product.
[0030] Silica fume is ultrafine silica fume from metallic silicon smelting. It has a SiO2 content ≥92%, an average particle size of 0.1–0.3 μm, and a specific surface area of 15000–22000 m². 2 / kg; Loose bulk density 180~250kg / m³ 3 Density: 2.20 g / cm³ 3 The loss on ignition is ≤6%, and there are no coarse particulate impurities. The particle size of silica fume is only 1 / 50 to 1 / 100 of that of cementitious materials, resulting in an extremely high specific surface area. Its core role in this invention is a dual mechanism of "filling + reaction": on the one hand, the ultrafine particles of silica fume can fill the micron-sized pores between cementitious material particles, acting as a physical filler and reducing the porosity of the matrix; on the other hand, the highly active SiO2 on the surface of silica fume dissolves under alkaline activation conditions, participating in the polymerization reaction to generate additional gel products, enhancing the density of the matrix and the interfacial bonding strength.
[0031] Quartz sand with a sieve size of 26–70 mesh. SiO2 ≥ 98.5%, mud content < 0.3%, bulk density 1.52–1.58 g / cm³. 3 Quartz sand, as a fine aggregate, plays a skeletal supporting role in the matrix. It forms a continuous gradation with solid waste powder. Quartz sand (26-70 mesh, about 210-710 μm) and solid waste powder (200-600 mesh, about 23-74 μm) form a "coarse-fine" complementary structure, allowing small particles to fill the voids between large particles, optimizing the bulk density of the aggregate system, and reducing the amount of cementitious material required to fill the voids.
[0032] The composite alkali activator is composed of NaOH solution and sodium silicate solution in a mass ratio of 17:36, with a total dosage of 265 parts. The NaOH solution has a concentration of 12 mol / L and is prepared by dissolving flake-shaped solid NaOH (industrial caustic soda flakes, purity ≥99%, 26-70 mesh flakes, free impurities ≤0.5%) in water. The sodium silicate solution has a modulus n=SiO2 / Na2O=3.2, a solid content of 40±2%, a Baumé degree of 38-42°Bé, and a viscosity of 120-180 mPa·s (25℃). The function of NaOH is to provide a high alkalinity environment (pH>14), allowing the glassy structure in industrial solid wastes such as blast furnace slag and fly ash to react with the OH-. - Under the influence of this process, depolymerization occurs, the Si-O and Al-O bonds break, and active silicon-aluminum species are released. Sodium silicate serves to provide added soluble silicon, which reacts with the dissolved Al. 3+ Ca 2+ The isocations undergo condensation polymerization to form a three-dimensional geopolymer network gel. The synergistic result of the two is that NaOH is responsible for "depolymerization" (destroying the original structure and releasing active ions), while sodium silicate is responsible for "condensation" (constructing a new structure and forming a gel network). The combination of depolymerization and condensation works together to maximize the conversion of active components in solid waste into geopolymer products with mechanical strength.
[0033] Solid waste micro powder is a 200-600 mesh micro powder obtained by air classification during the two-stage controlled ball milling process of solid waste coarse aggregate. Solid waste micro powder has the characteristic of "dual use": firstly, as a filler material, its particle size distribution (approximately 23-74 μm) precisely fills the voids left by quartz sand (approximately 210-710 μm), forming a continuous and compact packing, reducing the matrix porosity; secondly, as an auxiliary cementing material, its incompletely dissociated active components can further participate in the polymerization reaction under alkaline activation conditions, contributing a certain amount of cementitious strength. This design achieves complete resource utilization of ball mill byproducts (zero waste) while reducing the amount of quartz sand used, thus lowering raw material costs.
[0034] The shaped aggregate is produced by shaping coarse solid waste aggregate through a two-stage controlled ball mill. The coarse solid waste aggregate is selected from waste brown corundum aggregate with a particle size of 5–20 mm. The specific preparation process of the shaped aggregate is as follows: a mixture of cylindrical ceramic segments and triangular prism ceramic segments is used as the grinding media, with a mass ratio of coarse solid waste aggregate to grinding media of 1:(0.7–1.0). The linear velocity of the first stage of grinding is 1.5–1.6 m / s, and the grinding time is 12–18 min, which is used to passivate the sharp edges of the coarse solid waste aggregate. During this process, the local impact and grinding action of the grinding media on the surface of the coarse solid waste aggregate causes micro-fracture and peeling of the aggregate surface. At the same time, there are hardness differences between different mineral phases inside the coarse solid waste aggregate, with the soft phase peeling off preferentially and the hard phase protruding relatively, thus forming an irregular, uneven surface. The second stage of grinding involves a linear velocity of 1.2–1.4 m / s and a grinding time of 5–8 min. This is used to remove burrs from edges and corners, avoiding excessive grinding that could damage the already formed rough, uneven surface. After grinding, the ceramic abrasive and solid waste powder are separated by air classifier. The resulting shaped aggregate has a projected profile that is a polygon with smooth, rounded corners (i.e., the projected profile of the particles is a polygon or nearly polygon with smooth, rounded corners, with side lengths in the millimeter range). The radius of the rounded corners is 0.3–1.2 mm, the content of needle-like and flaky particles is ≤2%, and the crushing index is ≤6%. The 200–600 mesh powder obtained by air classifier separation is the solid waste powder of this invention. The aggregate morphology enhances the aggregate's strength through three levels: First, the rounded edges soften sharp corners, preventing stress concentration at these points under load and thus avoiding early microcrack initiation. Second, the rough, uneven surface creates a micro-mechanical interlocking between the shaped aggregate and the matrix. The matrix slurry penetrates the depressions on the rough surface and hardens to form a locking structure, making the aggregate less prone to pull-out or slippage under stress, significantly improving interfacial bond strength. Third, the rounded edges allow for a more compact aggregate arrangement within the matrix, reducing voids and consequently decreasing the total area and number of defects in the interfacial transition zone. Simultaneously, the 5–20 mm particle size range ensures the aggregate forms a robust skeletal support structure within the matrix, preventing interface defect concentration due to excessively large particle size or insufficient skeletal support due to excessively small particle size.
[0035] Nano-calcium carbonate has a primary particle size of 30–80 nm and a specific surface area of 350–450 m². 2 / kg, CaCO3≥97%, loss on ignition 42.0%~46.0%, free calcium oxide≤0.3%, true density 2.65~2.72g / cm³ 3The nano-calcium carbonate is spindle-shaped with a monodisperse content of ≥90%. It forms a "nano-micron" dual-scale filling system with the solid waste powder. The solid waste powder (micron-sized, 200–600 mesh, approximately 23–74 μm) fills the micron-sized voids between the aggregate and quartz sand; the nano-calcium carbonate (nano-sized, 30–80 nm) fills the submicron and nano-sized pores within the gel in the cementing system. This layered and scaled synergistic filling process gradually fills the pores in the matrix from the millimeter to the nanometer scale, significantly reducing the overall porosity and substantially improving the matrix density.
[0036] The modified steel fiber substrate is copper-plated steel fiber with a diameter of 0.18 mm and a length of 15 mm. The steel fiber pretreatment process is as follows: ultrasonic cleaning with anhydrous ethanol for 5 minutes to remove oil, followed by drying at 105℃; alkali etching by immersion in a 5% sodium hydroxide solution at room temperature for 20 minutes, followed by rinsing with water to remove surface alkali; immersion in a 5% sodium silicate aqueous solution for 5 minutes, followed by low-temperature drying at 60–70℃, forming a passivation film on the fiber surface. This passivation film, with a silicon-oxygen network as its framework, exhibits good chemical compatibility with the geopolymer matrix, delaying the corrosion process of the steel fiber in a high-alkali environment and maintaining the long-term adhesion performance between the fiber and the matrix interface. Within an appropriate doping range, the modified steel fiber can be uniformly dispersed within the matrix to form a spatially overlapping network. When the matrix is subjected to tensile cracking, the fiber crosses the crack surface to transfer stress, relying on bridging to prevent further crack propagation. Simultaneously, energy is dissipated through frictional slippage at the fiber-matrix interface, thereby improving the intrinsic brittleness of the geopolymer and effectively inhibiting the propagation of microcracks in the matrix.
[0037] The composite retarder consists of 0.3–0.6 parts of strontium nitrate and 0.06–0.15 parts of potassium fluorozirconate. Both strontium nitrate and potassium fluorozirconate are commercially available analytical grade reagents. Potassium fluorozirconate dissociates into [ZrF6] upon dissolving in water. 2- This complex ion can react with Al in the matrix. 3+ Complexation reactions occur, reducing the effective concentration of the aluminum source participating in the geopolymerization reaction; Sr nitrate slowly releases Sr in water. 2+ It can delay the contact reaction between particles and alkaline solution by physically adsorbing onto the surface of gelling particles or forming insoluble products. The combination of the two slows down the polymerization reaction rate through two pathways: liquid phase ion concentration and particle surface state, thus extending the slurry construction window.
[0038] Polycarboxylate superplasticizers are high-performance polycarboxylate superplasticizers with a water reduction rate of ≥25% and excellent alkali adaptability. The polycarboxylate superplasticizer molecule has a comb-like structure with multiple polar groups (such as carboxyl and sulfonic acid groups) on its main chain. These groups can adsorb onto the surface of gelling particles, causing the particles to acquire the same charge and generate electrostatic repulsion. Simultaneously, its long-chain side chains extend in solution, producing a steric hindrance effect. The combined effect of these two factors ensures thorough dispersion of the gelling particles in water, releasing free water trapped within the flocculated structure. This significantly reduces the yield stress of the slurry and improves its fluidity at the same water volume.
[0039] This silicone liquid defoamer is a polyether-modified silicone defoamer with an effective ingredient content ≥30%. It is resistant to strong alkaline systems, does not precipitate silicone, and is a liquid form. During the mechanical stirring of geopolymer slurries, due to the high alkalinity of the composite alkali activator and the stirring shearing action, a large number of microbubbles are easily entrained in the slurry. These bubbles form spherical pore defects after hardening, reducing the matrix density and mechanical properties. The polyether-modified silicone defoamer achieves defoaming and foam suppression by reducing the surface tension of the liquid film and disrupting the stability of bubbles. It can effectively eliminate bubbles introduced during stirring and reduce the porosity inside the matrix. Its polyether-modified structure ensures chemical stability in strong alkaline systems, preventing decomposition or silicone oil precipitation and avoiding negative impacts on the geopolymerization reaction.
[0040] The preparation method of the multi-solid waste synergistic geopolymer composite material of the present invention includes the following steps: Step (1) Preparation of composite alkali activator: Mix NaOH solution and sodium silicate solution evenly at a mass ratio of 17:36 to obtain composite alkali activator. The concentration of NaOH solution is 12 mol / L, and the modulus of sodium silicate solution is 3.2. Step (2), solid phase pre-dispersion: Weigh out the following by weight: metakaolin, fly ash, silica fume, quartz sand, solid waste powder, shaped aggregate, nano-calcium carbonate, composite retarder, and modified steel fiber. Add them to the mixer and dry mix at a low speed of 70 r / min for 2 min. The purpose of this step is to achieve full dispersion of modified steel fiber, nano-filler, composite retarder powder, and coarse and fine aggregate. By pre-mixing and dispersing the modified steel fiber with various powders and dry aggregates, the problem of fiber clumping, agglomeration, and uneven distribution in the liquid phase slurry is avoided from the root by relying on the barrier and lubrication effect of solid particles. After the fiber is uniformly dispersed in the matrix, it can form a continuous and stable spatial overlapping network, maximizing the fiber bridging, crack resistance, energy dissipation, and toughening effects. Step (3), Liquid-phase mixing: The composite alkali activator, polycarboxylate superplasticizer, and organosilicon liquid defoamer are premixed evenly and slowly poured into a mixer, and mechanically stirred at a medium speed of 90 r / min for 4 min. This step ensures that the liquid phase components are in full contact with the solid phase powder, thus activating the polymerization reaction. Step (4) Add blast furnace slag: After step (3) is completed, add blast furnace slag and mechanically stir at 150 r / min for 3 min. In this step, the blast furnace slag is added after the liquid phase is mixed to avoid premature contact with the composite alkali activator and rapid depolymerization and condensation reaction, effectively delaying the initial setting time of the slurry and avoiding problems such as loss of fluidity, pipe blockage, and dead corners in the early reaction of the geopolymer mixture. Step (5) Molding and curing: Transfer the mixture obtained in step (4) into a 100mm side length cube mold, vibrate for 30-60s, cover the surface with a film, let stand for 24h, demold, and cure according to standard to the specified age to obtain multi-solid waste synergistic geopolymer composite material.
[0041] Compared with traditional methods for preparing geopolymer materials, the advantages of this mixing process are: (1) segmented feeding to regulate the polymerization reaction, and superimposed strontium nitrate-potassium fluorozirconate composite retarding system to achieve dual retarding regulation; (2) dry material premixing and dispersing modified steel fibers to improve toughening uniformity and matrix integrity; the passivation film on the surface of the modified steel fibers isolates high-alkali matrix and chloride ions, and there is no risk of rust during long-term service.
[0042] Example 1
[0043] A multi-solid waste synergistic polymer composite material, by mass, is composed of the following raw materials: 280 parts blast furnace slag, 200 parts fly ash, 60 parts silica fume, 60 parts metakaolin, 265 parts composite alkali activator, 300 parts quartz sand, 200 parts solid waste micro powder (ball milled brown fused alumina micro powder), 900 parts shaped aggregate (obtained by two-stage controllable ball milling of waste brown fused alumina aggregate), 22 parts nano calcium carbonate, 25 parts polycarboxylate superplasticizer, 2 parts organosilicon liquid defoamer, 39 parts modified steel fiber, 0.3 parts strontium nitrate, and 0.06 parts potassium fluorozirconate.
[0044] The preparation method is as follows: Step (1) Preparation of shaped aggregate: Waste brown corundum aggregate with a particle size of 5-20 mm is mixed with grinding media at a mass ratio of 1:0.7 and placed in a drum ball mill for two-stage grinding. The grinding media is a mixture of cylindrical ceramic segments and triangular prism ceramic segments. The linear velocity of the first stage of grinding is 1.5 m / s, and the grinding time is 12 min; the linear velocity of the second stage of grinding is 1.2 m / s, and the grinding time is 5 min. After grinding, the ceramic abrasive and solid waste powder are separated by air classifier to obtain shaped aggregate, and the solid waste powder of 200-600 mesh (about 23-74 μm) is recovered for later use. Step (2), Preparation of composite alkali activator: Mix NaOH solution (concentration 12mol / L) and sodium silicate solution (modulus 3.2) at a mass ratio of 17:36 to obtain composite alkali activator; Step (3) Solid phase pre-dispersion: Weigh the above-mentioned parts by weight of metakaolin, fly ash, silica fume, quartz sand, solid waste powder obtained in step (1), shaped aggregate obtained in step (1), nano calcium carbonate, strontium nitrate, potassium fluorozirconate, and modified steel fiber and add them to the mixer. Dry mix at a low speed of 70 r / min for 2 min. Step (4), liquid phase mixing: the composite alkali activator, polycarboxylate superplasticizer and organosilicon liquid defoamer are premixed evenly, and slowly poured into the mixer, and mechanically stirred at a medium speed of 90r / min for 4min; Step (5) Add blast furnace slag: After step (4) is completed, add blast furnace slag and mechanically stir at 150 r / min for 3 min. Step (6) Molding and curing: Transfer the mixture obtained in step (5) into a 100mm side length cube mold, vibrate for 30s, cover the surface with a film, let stand for 24 hours, demold, and cure according to standard until the specified age.
[0045] Example 2
[0046] A multi-solid waste synergistic polymer composite material, by mass, is composed of the following raw materials: 280 parts blast furnace slag, 200 parts fly ash, 60 parts silica fume, 60 parts metakaolin, 265 parts composite alkali activator, 300 parts quartz sand, 200 parts solid waste micro powder (ball milled brown fused alumina micro powder), 900 parts shaped aggregate (obtained by two-stage controllable ball milling of waste brown fused alumina aggregate), 11 parts nano calcium carbonate, 25 parts polycarboxylate superplasticizer, 2 parts organosilicon liquid defoamer, 78 parts modified steel fiber, 0.4 parts strontium nitrate, and 0.12 parts potassium fluorozirconate.
[0047] The preparation method is the same as in Example 1.
[0048] Example 3
[0049] A multi-solid waste synergistic polymer composite material, by mass, is composed of the following raw materials: 280 parts blast furnace slag, 200 parts fly ash, 60 parts silica fume, 60 parts metakaolin, 265 parts composite alkali activator, 300 parts quartz sand, 200 parts solid waste micro powder (ball milled brown fused alumina micro powder), 900 parts shaped aggregate (obtained by two-stage controllable ball milling of waste brown fused alumina aggregate), 0 parts nano calcium carbonate, 25 parts polycarboxylate superplasticizer, 2 parts organosilicon liquid defoamer, 117.75 parts modified steel fiber, 0.6 parts strontium nitrate, and 0.15 parts potassium fluorozirconate.
[0050] The preparation method is the same as in Example 1.
[0051] Example 4
[0052] A multi-solid-waste synergistic polymer composite material, by mass, is composed of the following raw materials: 280 parts blast furnace slag, 200 parts fly ash, 60 parts silica fume, 60 parts metakaolin, 265 parts composite alkali activator, 300 parts quartz sand, 200 parts solid waste micro powder (ball-milled brown fused alumina micro powder), 850 parts shaped aggregate (obtained by two-stage controllable ball milling of waste brown fused alumina aggregate), 11 parts nano calcium carbonate, 25 parts polycarboxylate superplasticizer, 2 parts organosilicon liquid defoamer, 60 parts modified steel fiber, 0.45 parts strontium nitrate, and 0.08 parts potassium fluorozirconate.
[0053] The preparation method is the same as in Example 1.
[0054] Example 5
[0055] A multi-solid waste synergistic polymer composite material, by mass, is composed of the following raw materials: 280 parts blast furnace slag, 200 parts fly ash, 60 parts silica fume, 60 parts metakaolin, 265 parts composite alkali activator, 300 parts quartz sand, 200 parts solid waste micro powder (ball milled brown fused alumina micro powder), 950 parts shaped aggregate (obtained by two-stage controllable ball milling of waste brown fused alumina aggregate), 15 parts nano calcium carbonate, 25 parts polycarboxylate superplasticizer, 2 parts organosilicon liquid defoamer, 100 parts modified steel fiber, 0.5 parts strontium nitrate, and 0.10 parts potassium fluorozirconate.
[0056] The preparation method is the same as in Example 1.
[0057] Example 6
[0058] A multi-solid-waste synergistic polymer composite material, with the same raw material composition as in Example 1.
[0059] The difference between the preparation method and Example 1 is only that in step (1), waste brown corundum aggregate with a particle size of 5-20 mm is mixed with grinding media at a mass ratio of 1:1.0 and placed in a drum ball mill for two-stage grinding. The grinding media is a mixture of cylindrical ceramic segments and triangular prism ceramic segments. The linear velocity of the first stage of grinding is 1.6 m / s and the grinding time is 18 min; the linear velocity of the second stage of grinding is 1.4 m / s and the grinding time is 8 min. After grinding, the ceramic abrasive and solid waste powder are separated by air classifier to obtain shaped aggregate, and the solid waste powder of 200-600 mesh (about 23-74 μm) is recovered for later use.
[0060] Comparative Example 1 The only difference between the materials in this comparative example and those in Example 2 is that modified steel fibers are not added. All other components and preparation methods are the same as in Example 2.
[0061] Comparative Example 2 The only difference between the materials in this comparative example and those in Example 2 is that the coarse aggregate used is waste coal gangue aggregate, and the solid waste powder is ball-milled coal gangue powder. The remaining components and preparation methods are the same as in Example 2.
[0062] The purpose of setting up this comparative example is that waste coal gangue, as an industrial solid waste with a large emission volume, has the potential and representativeness to be used as an aggregate base material. It is listed as a comparative example to compare the actual performance differences of different types of solid waste coarse aggregates in the system of this invention.
[0063] Comparative Example 3 The only difference between the materials used in this comparative example and those in Example 2 is that the coarse solid waste aggregate is recycled building aggregate, and the solid waste powder is ball-milled recycled building aggregate powder. All other components and preparation methods are the same as in Example 2.
[0064] The purpose of setting up this comparative example is that recycled building aggregate is one of the main ways to utilize construction waste resources and is widely used in actual engineering. It is listed as a comparative example to compare the actual performance differences of different types of solid waste coarse aggregate in the system of this invention.
[0065] Comparative Example 4 The only difference between the materials used in this comparative example and those in Example 2 is that the coarse solid waste aggregate used is unprocessed raw waste brown corundum aggregate. All other components and preparation methods are the same as in Example 2.
[0066] Comparative Example 5 The only difference between the materials in this comparative example and those in Example 2 is that the solid waste coarse aggregate used is waste brown corundum aggregate that has undergone excessive ball milling. The specific process of excessive ball milling is as follows: a mixture of cylindrical and triangular prism ceramic segments is used as the grinding media, the mass ratio of solid waste coarse aggregate to grinding media is 1:0.7, continuous ball milling is performed for 40 minutes, and the roller linear speed is 1.5 m / s. The resulting aggregate surface is polished into a smooth spherical surface. The remaining components and preparation methods are the same as in Example 2.
[0067] Comparative Example 6 The only difference between the materials in this comparative example and those in Example 2 is that strontium nitrate and potassium fluorozirconate are not added. The remaining components and preparation methods are the same as in Example 2.
[0068] Comparative Example 7 The materials used in this comparative example are the same as those in Example 2. The only difference between this comparative example and Example 2 is that steps (5) and (3) are combined, i.e., the blast furnace slag and other dry materials are added together to the mixer in step (3) for dry mixing and dispersion, and the subsequent steps remain unchanged. The remaining preparation steps are the same as those in Example 2.
[0069] The products obtained from each embodiment and comparative example are tested below, and the test results are analyzed.
[0070] Compressive strength test: Static compressive strength test was conducted according to GB / T 17671-2020 "Test Method for Strength of Cement Mortar (ISO Method)". The specimen size was 100mm×100mm×100mm cube, and the loading speed was 2.4kN / s. The compressive strength was tested at 3d, 7d, and 28d.
[0071] Setting time test: The initial setting time was tested according to GB / T 1346-2024 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement" and measured using a Vicat apparatus.
[0072] The performance test results of Examples 1-6 and Comparative Examples 1-7 are shown in Table 1.
[0073] Table 1 Performance test results of Examples 1-6 and Comparative Examples 1-7
[0074] As shown in Table 1: (1) Comparing Examples 1-5 with Comparative Example 1, it can be found that the incorporation of modified steel fibers has a significant effect on improving the compressive strength of the geopolymer composite material. The 28-day compressive strength of Comparative Example 1 (without modified steel fibers) is 105.7 MPa. The 28-day compressive strength of Example 1 (with 39 parts of modified steel fibers) is 135.6 MPa, which is 28.3% higher than that of Comparative Example 1. The 28-day compressive strength of Example 2 (with 78 parts of modified steel fibers) is 142.1 MPa, which is 34.4% higher than that of Comparative Example 1, and is the highest among all groups. The 28-day compressive strength of Example 3 (with 117.75 parts of modified steel fibers) is 133.8 MPa, which is 26.6% higher than that of Comparative Example 1. The 28-day compressive strengths of Example 4 (with 60 parts of modified steel fiber) and Example 5 (with 100 parts of modified steel fiber) were 139.5 MPa and 137.2 MPa, respectively, both significantly higher than those of Comparative Example 1. The main reason is that the modified steel fiber forms a continuous spatial overlapping network inside the matrix, which plays a bridging, crack-blocking, and energy-dissipating role when cracking occurs, effectively inhibiting the propagation of microcracks. When the amount of modified steel fiber increases from 39 parts to 78 parts, the fiber overlapping network gradually improves and the strength continues to increase; when the amount continues to increase to more than 100 parts, the fiber volume content is too large, the workability of the slurry decreases, the molding density decreases, and the local defects increase, which offsets part of the fiber toughening gain, and the compressive strength drops, but still remains at a high level. In summary, the optimal amount of modified steel fiber is about 78 parts. (2) By comparing Example 2, Comparative Example 2, and Comparative Example 3, it can be seen that under the condition that the fiber content is 78 parts, the selection of solid waste coarse aggregate has a significant impact on the material strength. Example 2 uses waste brown fused alumina aggregate, whose matrix is high-hardness Al2O3. It has a low crushing index, is resistant to strong alkali erosion, and has optimal elastic modulus matching with the matrix. After two-stage controlled ball milling, it exhibits a near-polygonal morphology, providing ample mechanical interlocking and few defects in the interface transition zone. Its 28-day compressive strength is 142.1 MPa. Comparative Example 3 uses recycled building aggregate, which contains pores and microcracks from the original cement mortar. The aggregate itself has low strength, and internal failure occurs first under stress, resulting in lower strength than the waste brown fused alumina system (28-day compressive strength 116.4 MPa). Comparative Example 2 uses waste coal gangue aggregate. The original coal gangue has a complex mineral composition, well-developed internal pores, and uneven mineral activity. The alkali activation process easily produces micro-expansion defects, resulting in poor mechanical properties and easy breakage under load. Its 28-day compressive strength is the lowest among the three groups (98.3 MPa). Therefore, to prepare high-performance (28d compressive strength ≥120MPa) multi-solid waste synergistic geopolymer composites, waste brown corundum aggregate should be selected as coarse solid waste aggregate. (3) By comparing Example 2, Comparative Example 4 and Comparative Example 5, it can be found that under the condition that the fiber content is 78 parts, the shape of the aggregate has a significant impact on the strength of the geopolymer composite.Comparative Example 4 used unmilled virgin aggregate with sharp edges. Under load, stress concentration occurred at these sharp corners, rapidly inducing interfacial microcracks and premature material failure under pressure. Its 28-day compressive strength was 112.6 MPa, the lowest among the three groups. Comparative Example 5 used excessively milled aggregate, with a smooth spherical surface. The aggregate and matrix were bonded only by weak friction, lacking the mechanical interlocking effect provided by the textured surface. This significantly reduced interfacial adhesion, resulting in a 28-day compressive strength of 120.8 MPa, lower than the aggregate shaped by two stages of controlled ball milling. Example 2 used shaped aggregate obtained after two stages of controlled ball milling. This blunted the sharp edges while retaining the textured surface, eliminating stress concentration sources and maintaining the interlocking between the aggregate and matrix. Its 28-day compressive strength was 142.1 MPa, showing the most significant improvement. (4) Comparing Example 2 with Comparative Example 6 reveals that adding strontium nitrate and potassium fluorozirconate significantly increases the initial setting time without negatively impacting later strength. The initial setting time of Comparative Example 6 (without strontium nitrate and potassium fluorozirconate) was only 35 min, while the initial setting time of Example 2 (with 0.4 parts strontium nitrate and 0.12 parts potassium fluorozirconate) was extended to 85 min, an increase of 50 min. Simultaneously, the 28-day compressive strength of Comparative Example 6 was 138.6 MPa, and the 28-day compressive strength of Example 2 was 142.1 MPa, which are essentially equivalent, indicating that the composite retarder significantly extends the setting time without causing later strength loss. The mechanism lies in the dissociation of potassium fluorozirconate to produce [ZrF6]. 2- This complex ion can react with Al in the matrix. 3+ Complexation reactions occur, reducing the effective concentration of the aluminum source participating in the geopolymerization reaction; Sr nitrate slowly releases Sr in water. 2+ It can be physically adsorbed onto the surface of the cementitious particles or form insoluble products, thus delaying the contact reaction between the particles and the alkaline solution. The combination of the two slows down the polymerization reaction rate and prolongs the construction window of the slurry. (5) Comparing Example 2 with Comparative Example 7, it can be found that the feeding sequence of blast furnace slag has a significant impact on the material properties. Example 2 adopts a delayed feeding process, with an initial setting time of 85 min and a 28-day compressive strength of 142.1 MPa. Comparative Example 7 adds blast furnace slag and other dry materials together in step (3) (i.e., no delayed feeding), shortening the initial setting time to 45 min and reducing the 28-day compressive strength to 126.8 MPa. The reason is that blast furnace slag has high activity. If it comes into contact with the composite alkali activator in the solid pre-dispersion stage, a rapid reaction will occur in advance, resulting in a significant reduction in the initial setting time of the slurry and an aggravation of fluidity loss. At the same time, the gel network structure formed by the early rapid reaction is uneven, and the internal defects increase, leading to a decrease in strength in the later stage. This invention employs a delayed blast furnace slag feeding method to avoid premature contact between highly active blast furnace slag and high-concentration composite alkali activator, effectively delaying the initial setting time of the slurry. At the same time, it ensures that the polymerization reaction takes place under more uniform conditions, thereby obtaining a denser microstructure and higher mechanical strength.
[0075] In summary, this invention uses blast furnace slag, fly ash, silica fume, and metakaolin as cementing materials, and employs a composite alkali activator to fully activate the cementing activity of various industrial solid wastes. The coarse aggregate from the solid waste is shaped through a two-stage controllable ball mill with rounded edges to obtain a roughened aggregate with blunted corners, and is combined with micro-powdered solid waste from the ball mill to construct a dense packing gradation. Nano-calcium carbonate is introduced to fill micropores and optimize matrix density. Alkali etching and sodium silicate treatment are used to modify steel fibers for synergistic toughening. A composite retarder of strontium nitrate and potassium fluorozirconate is used to regulate the slurry setting time. Combined with the delayed feeding process of blast furnace slag, multiple modification mechanisms work synergistically to achieve a simultaneous improvement in the comprehensive performance of the geopolymer material, including high strength, high density, high toughness, and a long construction window. Using industrial solid waste as the core aggregate and cementing raw material, this invention is green, low-carbon, and has lower raw material costs, making it widely applicable to civil defense and air-blast protection projects, high-rise buildings, bridges and tunnels, deep-water ports and wharves, and various special structural projects in corrosive environments.
[0076] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention, or modify them into equivalent embodiments, without departing from the scope of the technical solutions of the present invention. Therefore, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention shall still fall within the protection scope of the technical solutions of the present invention.
Claims
1. A multi-solid waste synergistic polymer composite material, characterized in that, By weight, it contains the following raw materials: 280 parts blast furnace slag, 200 parts fly ash, 60 parts silica fume, 60 parts metakaolin, 265 parts composite alkali activator, 300 parts quartz sand, 200 parts solid waste powder, 850-950 parts shaped aggregate, 0-22 parts nano calcium carbonate, 25 parts polycarboxylate superplasticizer, 2 parts organosilicon liquid defoamer, 39-117.75 parts modified steel fiber, and 0.36-0.75 parts composite retarder; The composite alkali activator is composed of a NaOH solution and a sodium silicate solution in a mass ratio of 17:
36. The shaped aggregate is obtained by shaping solid waste coarse aggregate through a two-stage controllable ball mill. The projection is a polygonal shape with smooth transitions at the edges and corners. The radius of the rounded transition at the edges and corners is 0.3 to 1.2 mm, and the surface has a textured surface. The solid waste powder is the powder obtained by air separation during the ball milling and shaping process of the solid waste coarse aggregate. The solid waste coarse aggregate is selected from waste brown fused alumina aggregate, and the solid waste micro powder is ball-milled brown fused alumina micro powder. The modified steel fiber has a passivation film on its surface. The modified steel fiber is prepared by the following process: using copper-plated steel fiber with a diameter of 0.18 mm and a length of 15 mm as the substrate, it is ultrasonically cleaned with anhydrous ethanol for 5 min to remove oil, dried at 105°C, immersed in a 5% sodium hydroxide solution at room temperature for 20 min for alkaline etching, washed with water to remove surface alkali, and then immersed in a 5% sodium silicate aqueous solution for 5 min. It is then dried at a low temperature of 60-70°C to obtain the modified steel fiber with a passivation film on its surface. The composite retarder is composed of 0.3 to 0.6 parts of strontium nitrate and 0.06 to 0.15 parts of potassium fluorozirconate.
2. The multi-solid waste synergistic geopolymer composite material according to claim 1, characterized in that, In the composite alkali activator, the concentration of the NaOH solution is 12 mol / L, and the modulus of the sodium silicate solution is 3.
2.
3. The multi-solid waste synergistic geopolymer composite material according to claim 1, characterized in that, The shaped aggregate is prepared by the following process: a mixture of cylindrical ceramic segments and triangular prism ceramic segments is used as the grinding medium, and the mass ratio of solid waste coarse aggregate to grinding medium is 1:(0.7~1.0). It is ground in two stages, wherein the linear velocity of the first stage of grinding is 1.5~1.6m / s and the grinding time is 12~18min, which is used to passivate the sharp edges and corners of the solid waste coarse aggregate and form an uneven surface; the linear velocity of the second stage of grinding is 1.2~1.4m / s and the grinding time is 5~8min, which is used to remove burrs from the edges and corners.
4. The multi-solid waste synergistic geopolymer composite material according to claim 1, characterized in that, The average particle size of the nano-calcium carbonate is 30–80 nm, and the specific surface area is 350–450 m². 2 / kg, CaCO3 content ≥97%; The particle size of the solid waste powder is 200-600 mesh.
5. The multi-solid waste synergistic geopolymer composite material according to claim 1, characterized in that, The blast furnace slag is S95 grade water-quenched granulated blast furnace slag powder with a specific surface area of 420-460 m². 2 / kg; The fly ash is Grade I low-calcium fly ash, with free calcium oxide ≤1.0% and a specific surface area of 380–430 m². 2 / kg; The silica fume has a SiO2 content of ≥92% and an average particle size of 0.1–0.3 μm; The metakaolin is obtained by calcining kaolin at 600℃ for 2 hours, and the content of amorphous active aluminum phase is ≥85%.
6. A method for preparing a multi-solid waste synergistic polymer composite material, characterized in that, The method for preparing the multi-solid-waste synergistic geopolymer composite material according to any one of claims 1-5 comprises the following steps: Step (1) Preparation of composite alkali activator: Mix NaOH solution and sodium silicate solution evenly to obtain composite alkali activator; Step (2), solid phase pre-dispersion: add metakaolin, fly ash, silica fume, quartz sand, solid waste powder, shaped aggregate, nano calcium carbonate, composite retarder and modified steel fiber into a mixer and dry mix and disperse. Step (3), Liquid phase mixing: The composite alkali activator, polycarboxylate superplasticizer and organosilicon liquid defoamer are premixed evenly, poured into a mixer and stirred evenly; Step (4) Add blast furnace slag: After step (3) is completed, add blast furnace slag and stir to mix well; Step (5) Molding and curing: Transfer the mixture obtained in step (4) into the mold, vibrate it, cover the surface with a film, let it stand, demold it, and cure it to the specified age.
7. The preparation method according to claim 6, characterized in that, In step (2), the dry mixing speed is 70 r / min and the time is 2 min; In step (3), the stirring speed is 90 r / min and the time is 4 min; In step (4), the stirring speed after adding blast furnace slag is 150 r / min and the time is 3 min.
Citation Information
Patent Citations
Anticorrosion expansion compacting agent composition and preparation method thereof
CN102690077A
Geopolymeric concrete and manufacturing method for eco-friendly non-cement of new construction materials using recycled aggregate from waste of constrcution
KR101256834B1